Exponential stability results for fixed and random type impulsive Hopfield neural networks. (2016) - Vinodkumar, A.; Rakkiyappan, R.
This article presents the exponential stability results on impulsive Hopfield neural networks (IHNNs) via variation of parameters and fixed point theory. The study is mainly considering two types of IHNNs, namely fixed and random type IHNNs. A numerical example is also presented to validate the theoretical results.